1994
DOI: 10.1128/mcb.14.2.934
|View full text |Cite
|
Sign up to set email alerts
|

Multiple silencer elements are involved in regulating the chicken vimentin gene.

Abstract: Vimentin, a member of the intermediate filament protein family, exhibits tissue-as well as developmentspecific expression. Transcription factors that are involved in expression of the chicken vimentin gene have been described and include a cis-acting silencer element (SE3) that is involved in the down-regulation of this gene (F. X. Farrell, C. M. Sax, and Z. E. Zehner, Mol. Cell. Biol. 10:2349Biol. 10: -2358Biol. 10: , 1990. In this study, we report the identification of two additional silencer elements (SE1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
(80 reference statements)
3
23
1
Order By: Relevance
“…Silencer activity has been implicated in the regulation of the vimentin gene, another intermediate filament gene (12,17,50,59). However, the expression of vimentin in F9 cells, the absence of apparent sequence homology to the K18 silencers, and the activity of the vimentin silencers in several somatic cell types suggest that the silencer elements of the two types of intermediate filament genes are probably mediated by different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Silencer activity has been implicated in the regulation of the vimentin gene, another intermediate filament gene (12,17,50,59). However, the expression of vimentin in F9 cells, the absence of apparent sequence homology to the K18 silencers, and the activity of the vimentin silencers in several somatic cell types suggest that the silencer elements of the two types of intermediate filament genes are probably mediated by different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of the PNR element-mediated gene repression remains to be determined, the presence of multiple Ets-binding sites as a palindrome at the downstream position of the ␣-MHC gene and the involvement of the upstream sites would indicate that it might be a requirement for the physical hindrance and/or conformational rigidity needed for the negative control of gene transcription initiation. Similarly, other studies have shown a requirement of multiple sites for silencing the myosin light chain-2, collagen-II, and vimentin gene expression (10,12,53).…”
Section: Vol 18 1998 Tissue-restricted Expression Of ␣-Mhc Gene 7249mentioning
confidence: 99%
“…That the vimentin promoter sequence is functionally conserved is shown by the identification of numerous transcription sites on the human promoter in mouse cells [17,18,52,53] and in the chicken promoter in mouse and human cells [19,32,51]. Transgenic mouse studies also suggested that regulation of the human promoter in mouse cells and tissues parallels the endogenous gene [47].…”
Section: Discussionmentioning
confidence: 94%
“…Both r3 and r3T cells were used for these analyses, since they have similar levels of vimentin mRNA expression: we compared these cells to NIH3T3, which express 100-fold higher levels of vimentin in the absence of TGFβ ( Figure 3D). The human vimentin promoter has been characterized in a variety of fibroblasts, and the well studied 1.5 kb promoter contains both enhancer and silencer elements [17,19,20]. We initially examined three promoter constructs containing 1500, 411 and 268 nucleotides of promoter sequence fused to a CAT reported gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation